Modellinng, control and experimental validation for motorised wheel speed control - Razak, Muhammad Shukri Azizi; Ahmad, Fauzi; Che Hasan, Mohd Hanif (Penerbit Universiti Teknikal Malaysia Melaka, 2023)
This paper presents the experimental validation of three-phase motorized wheel (MW) mathematical model. The research which ignited from the lack of validation of MW was started from the simulation that developed utilizing MATLAB/Simulink software. A speed control based Proportional-Integral (PI) controller was then implemented to the simulation to verify the effectiveness of the mathematical model. Several simulation tests namely step, sinewave and sawtoothfunction at 10, 20, and 30 km/h respectively have been conducted. In order to ensure the reliability of the simulation model, a series of validation tests were performed using the same tests method conducted in the simulation. Various parameters, such as speed, distance, current, torque, and voltage, were measured during the tests. The results indicated that the simulation results are able to mimic the trend of experimental data with an acceptable error rate of less than 5%.